k-17=-(17-k)

Simple and best practice solution for k-17=-(17-k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-17=-(17-k) equation:


Simplifying
k + -17 = -1(17 + -1k)

Reorder the terms:
-17 + k = -1(17 + -1k)
-17 + k = (17 * -1 + -1k * -1)
-17 + k = (-17 + 1k)

Add '17' to each side of the equation.
-17 + 17 + k = -17 + 17 + 1k

Combine like terms: -17 + 17 = 0
0 + k = -17 + 17 + 1k
k = -17 + 17 + 1k

Combine like terms: -17 + 17 = 0
k = 0 + 1k
k = 1k

Solving
k = 1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
k + -1k = 1k + -1k

Combine like terms: k + -1k = 0
0 = 1k + -1k

Combine like terms: 1k + -1k = 0
0 = 0

Simplifying
0 = 0

The solution to this equation could not be determined.

See similar equations:

| (2x^2-15x-15)/(2x+3) | | -21/25y | | y-11=2(x-4) | | y-13=6(x-1) | | (x/4)*3=225 | | y-11=5(x-4) | | 3/2a+5/3a-13/6a-2/3=5/6 | | 5(r+6)=-5(r+-4) | | -31=3x+9-8 | | 0.3(y-2)=0.4(1+y) | | 20=2y-16 | | 78x^2=x-7 | | 5.7x=49.59 | | (x+3)(x-7)=(2x+5)(x-7) | | X/4=225 | | -2(k-1)=8(1+k) | | -x^2=1-2x | | 2x^2-24-6x=x^2-4x | | 3/x-x=x/10-5/2 | | 4x^2-25x=21 | | 4x-25x=21 | | 3x^2=22x+16 | | 3y/2x | | -2(k-1)=8+(1+k) | | -7/-5 | | 126=0.05x+26 | | ((9y^2)4x)12xy= | | 126.00=0.05x+26 | | 3/8+2/3 | | 5x+10y=7 | | 7y=18x+5(3+2) | | 123+889= |

Equations solver categories